Hypopigmented Mycosis Fungoides in an 11-Year-Old Palestinian Boy - Duha Rabi; Balqis Shawer; Ahmad Rabee; Mohammad Qudaimat; Mohammad Milhem; Izzeddin Bakri (Case Reports in Dermatological Medicine)
Cutaneous T-cell lymphoma (CTCL) is a lymphoproliferative disorder of the skin. The most common subtype of CTCL in pediatrics is mycosis fungoides (MF). There are multiple variants of MF. The hypopigmented variant represents more than 50% of MF cases in pediatrics. Misdiagnosis of MF can occur because it may resemble other benign skin pathologies. This is a case of an 11-year-old Palestinian boy presented with generalized nonpruritic hypopigmented maculopapular patches with progressive course for 9-months. Biopsy samples from a hypopigmented patch revealed appearances diagnostic of MF. Immunohistochemical staining was positive for CD3 and CD7 (partial) and a mixture of CD4 and CD8 positive cells. The patient’s case was managed with narrowband ultraviolet B (NBUVB) phototherapy. After a few sessions, the hypopigmented lesions improved significantly.